(untitled) (African Journal of Biomedical Research, 2022)
Lead is a systemic toxicant that affects virtually every organ system, primarily the central nervous system, through an increase in the production of reactive oxygen species (ROS). This increase in ROS overwhelms the natural antioxidant system of the body leading to oxidative stress. Some plants such as Vernonia amygdalina have been reported to possess antioxidant activity which counteracts the damage induced by free radicals. Accordingly, this study was designed to investigate the possible protective activity of aqueous Vernonia amygdalina leaf extract against lead-induced neurotoxicity in adult Wistar rats. Thirty Wistar rats were randomised into six groups (A-F) consisting of five rats each for a study period of 28 days. Group A served as the control group, Group B was administered with 100mg/kg body weight of lead only, Groups C and D were pretreated with 200mg/kg and 400mg/kg bodyweight of aqueous Vernonia amygdalina leaf extract and 100mg/kg body weight of lead respectively. Groups E and F were administered with 200mg/kg and 400mg/kg bodyweight of aqueous Vernonia amygdalina leaf extract only. The Open field and Novel Object Recognition tests were assessed and thereafter, the cerebellum, cerebrum and hippocampus were harvested for histological examination. Results showed a significant decrease in the body and brain weights, ambulation, rearing and discrimination index as well as a conversely significant increase in grooming and immobility in lead-treated rats. Histological examination of lead-alone treated groups showed loss of some Purkinje cells in the cerebellum, degenerating pyramidal cells in the cerebrum and altered morphology with pyknotic nuclei in the hippocampus. Pretreatment of rats with Vernonia amygdalina attenuated lead-induced alterations to body and brain weights, neurobehavioural activities and tissue histomorphology, thus indicating a potent protective activity. These findings provide the first research evidence that Vernonia amygdalina protects against lead-induced neurotoxicity in Wistar rats.